Service Quality And Customer Satisfaction: Rapid Kuantan In Kuantan Route, Malaysia - Liu, Yao; Fadilah, Siali; Mohd Ridzuan, Darun; Muhammad Firdaus, Ismail (2014)
Public transportation is supposed to bring more convenience to customers in urban and rural areas. However, continuous complaints about Rapid Kuantan were exposed in internet, which causes the bad public image of the two-year-old public transport. This study aims to evaluate customer satisfaction towards the service quality provided by the Rapid Kuantan from the dimensions of reliability, tangibility, responsiveness, assurance and empathy. Survey questionnaire was conducted from 150 passengers from three routes (Route 100, 200 and 300) of Rapid Kuantan. The derived results verify that the five service quality dimensions positively contribute to customer satisfaction at Rapid Kuantan, especially in the three routes. Thus, it implies that to enhance customer satisfaction, the Rapid Kuantan could exert more efforts on the five service quality dimensions, especially the weakest one Reliability.